Relational Bonding and Relationship Satisfaction in Sustaining Franchise Relationships in the Food and Beverage Sector - Uripi, Cahyaningtyas Ria; Zuhaena, Fatwa; Siwi, Sri Rahayu (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study examines the effects of relational bonding and relationship satisfaction on long-term relationships in the food and beverage franchise sector in Purwokerto, Indonesia. Relational bonding is defined through three dimensions: social, financial, and structural bonding. A survey of 113 franchise business owners was conducted using non-probability sampling, and the data were analyzed with Structural Equation Modeling (SEM) through AMOS. The findings show that all three dimensions of relational bonding significantly influence both relationship satisfaction and long-term relationships. Furthermore, relationship satisfaction plays a mediating role in sustaining franchise partnerships. These results contribute to franchise research by confirming the importance of relationship marketing and exchange-based perspectives, while offering practical implications for franchisors to build stronger interpersonal ties, provide fair financial incentives, and deliver reliable service support. The study is limited to one sector and region, and future research should explore other sectors and broader contexts to validate these findings.